An Initial Investigation of the Generalization of a School-Based Social Competence Intervention for Youth with High-Functioning Autism. (16th November 2011) - Schmidt, Carla; Stichter, Janine P.; Lierheimer, Kristin; McGhee, Stephanie; O'Connor, Karen V.
Abstract : This study evaluated the impact of generalization of the Social Competence Intervention-Adolescent (SCI-A) curriculum in a school setting for individuals with high-functioning autism or Asperger's Syndrome (N = 6 ). This study examined to what degree the generalization of the SCI-A curriculum could be measured when delivered in a school setting. Across the six participants preliminary results suggest improvement on teacher reports of social skills and executive functioning. Some improvements were also evident in direct measures of facial-expression recognition. Data collected in the nonintervention settings indicated that some generalization of social interaction skills may have occurred for all six participants. Future research directions are discussed.